Meningkatan Aktivitas Dan Motivasi Belajar Menggunakan Model PBL, TGT, TALKING STICK Di SDN Sungai Miai 2 Banjarmasin - Reginatama Putri; Metroyadi (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem of this research is the low activity and motivation of students in class, especially in science content. This study aims to increase student learning activity and motivation. This study used the approach and type of Classroom Action Research carried out in 4 meetings and the subjects studied were fourth grade students at SDN Sungai Miai 2 Banjarmasin. The types of data in this study are qualitative and quantitative. Qualitative comes from student activity and motivation, while quantitative comes from learning outcomes. The results of this study showed that the teacher's activity at the first meeting was quite good, the second and third meetings were in the good category, and the fourth meeting was in the very good category. Student activity at meeting I was in the quite active category, meeting II was in the active category, meeting III was in the active category, and meeting IV was in the very active category. Student motivation at meeting I scored 57% in the active category, meetings II, III, and IV scored 100% in the very motivated category. Classical completeness student learning outcomes at meeting I score 19%, II score 29%, III score 81%, IV score 100%. Based on these results, the researcher concluded that using the PBL, TGT, and Talking Stick models in science content could increase activity, motivation, and learning outcomes from the cognitive, affective, and psychomotor aspects.